The Legal Liability of the Maritime Carrier and the Economic Consequences of Goods Remaining at the Aden Port Container Terminal - Ashraf A. Qardash; Ali Abdulrahman Al-Awli; Ahmed E. Hafez (International Journal of Law Research and Studies, 2026)
Updating the Yemeni maritime legislation in line with the Hamburg Rules and the Rotterdam Rules has become an urgent necessity to harmonize the national framework with contemporary international standards, and to clearly regulate the point at which risk and liability transfer between the carrier, the consignee, and the port operator. Introducing precise definitions for delay-related provisions and explicit regulations for abandoned cargo (including notification periods, fair modes of disposition, and safeguarding the port’s financial entitlements), alongside transparent fee structures for delay penalties and effective alternative dispute resolution mechanisms, would significantly reduce conflicts related to cargo retention in port yards, facilitate fair and prompt settlement of maritime disputes, minimize storage costs, and enhance the efficiency and competitiveness of Aden Port within regional supply chains. This research seeks to propose a set of practical measures enabling the port to take action regarding abandoned cargo after a defined period, as well as coordination and procedural improvements that reduce clearance time and enhance information flow among stakeholders. Achieving these objectives not only safeguards the rights of the port, cargo owners, and carriers, but also strengthens the efficiency of the logistics system and reinforces Aden Port’s position as a competitive regional hub capable of responding to the requirements of modern maritime trade. The study found that Yemeni maritime law has drawn upon the principles of several international laws and conventions regulating maritime transport activities. However, the legislation still requires modernization to keep pace with the rapid developments in international legal systems, particularly those associated with technological advances and automation, which have created a new operational reality that must be reflected in the language and provisions of the law. The study recommends expanding the scope of the current Yemeni port regulations to comprehensively address all operational and service-related aspects of port activities, both navigational and logistical/administrative. It also calls for a thorough review and update of Yemeni maritime law to incorporate international rules that reflect the accelerating developments in maritime transport and to provide practical solutions for the persistent issue of abandoned and long-stored cargo that consignees have failed to clear.